Vaccine ready for small ruminants - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Several laboratories in Africa have started production of vaccine against 'peste des petits ruminants' also known as pseudo-rinderpest. In the last year, production units and marketing facilities have been set up in laboratories in Botswana,...